‘Sun, Sand and Sensation’ - Fettes, Carolyn (Homœopathic Links, 2015)
‘The other song’ International Academy of Advanced Homeopathy is a universal education platform that welcomes all approaches in homeopathy to provide students, interns and practitioners with advanced clinical training. The Academy, headed by Dr. Rajan Sankaran and supported by his colleagues, is a converging point where some of the best minds in the field of homeopathy make invaluable contributions towards the well-being of patients and the learning of doctors locally and internationally. At the ‘Sun, Sand and Sensation’ workshop in Goa, teachers from ‘The Other Song’ academy gave presentations.
Keywords: The Other Song Academy; Sensation method; Genius; Carcinosinum; Paraffinum; Rosaceae; Thyroidinum